Association of Mean Platelet Volume with Response to Neoadjuvant Chemotherapy in Rectal Cancer Patients - Elfiani Rusadi; Jelita Siregar; Adi Muradi Muhar (Indonesian Journal of Global Health Research, 2026)
Rectal cancer is one of the most common malignant neoplasms in humans and ranks as the second most frequent cancer of the large intestine. The management of rectal cancer requires a multidisciplinary approach, including surgery, chemotherapy, and radiotherapy administered either before or after surgery to improve the chances of cure. Mean Platelet Volume (MPV) reflects platelet size and is associated with platelet production and activation. Platelet activation plays a crucial role in the development and progression of malignancy. This study aimed to determine the relationship between Mean Platelet Volume (MPV) and the response to neoadjuvant chemotherapy in patients with rectal cancer, as assessed using the Response Evaluation Criteria in Solid Tumors (RECIST). This study was an analytical study with a cross-sectional design, in which several variables were measured simultaneously at a single point in time. Data were collected from outpatients attending the Digestive Surgery Clinic at Adam Malik General Hospital, Medan. A total of 81 patients who met the study inclusion criteria were enrolled using a consecutive sampling method. Data were analyzed using the Shapiro–Wilk test to assess the normality of data distribution. One-way ANOVA or the Kruskal–Wallis test was used to analyze differences between qualitative variables, as appropriate. Receiver Operating Characteristic (ROC) analysis was performed to determine the diagnostic performance of Mean Platelet Volume (MPV). A total of 81 patients were included in this study, with the majority being female (n = 41). The mean age of the study subjects was 53.9 years. Tumors were most commonly located in the proximal rectum (33 patients), and the predominant histopathological differentiation was well differentiated, observed in 53 patients. Most patients with low MPV values (<8.6 fL) demonstrated a better response to chemotherapy, characterized by partial response and stable disease, whereas patients with high MPV values (≥8.6 fL) more frequently experienced progressive disease. There was no statistically significant association between Mean Platelet Volume (MPV) and response to neoadjuvant chemotherapy in patients with rectal cancer, as assessed using the RECIST criteria (p = 0.075). However, clinically, patients with lower MPV values tended to demonstrate a better therapeutic response compared with those with higher MPV values.